Evaluation of Efficacy and Safety of Etanercept and Etanercept + Methotrexate Therapy in Patients with Juvenile Idiopathic Arthritis without Systemic Manifestations - T. M. Bzarova; Ye. I. Alekseeva; S. I. Valieva; R. V. Denisova; K. B. Isaeva; Ye. G. Chistyakova; A. M. Chomakhidze; T. V. Sleptsova; A. N. Fetisova; O. L. Lomakina; M. A. Soloshenko (Вопросы современной педиатрии, 2016)
Background: At present, it is urgent to find ways to overcome the inefficiency of and intolerance to the methotrexate therapy in patients with juvenile idiopathic arthritis (JIA). A promising method is the use of TNF-alpha inhibitors as monotherapy.Objective: Our aim was to evaluate the efficacy and safety of etanercept monotherapy and treatment with etanercept and methotrexate in patients with JIA without systemic manifestations.Methods: Observational study with retrospective assessment of the treatment of patients who received etanercept — the treatment group (n = 55) and the combination of etanercept and methotrexate — the control group (n = 136). The efficacy was evaluated for 3 years using the pediatric criteria of the American College of Rheumatology (ACR), remission criteria by C. Wallace and index JADAS71.Results: Total amount of patients with JIA without systemic manifestations under study is 191. As early as 1 month after the first etanercept injection, clinical and laboratory parameters of disease activity significantly decreased in 83 and 77% and functional ability of joints improved in 87 and 74% of patients treated with TNF- inhibitor and its combination with methotrexate. After 6 months, the improvement according to the ACR pediatric criteria 30/50/70 was recorded in 98/98/96 and 96/95/86%; inactive stage of the disease/remission was recorded in 44 and 24% of patients who received etanercept and etanercept + methotrexate. After 1 year, the improvement was recorded in 100 and 100/98/93% of patients in the treatment group and the control group and inactive stage of the disease/remission — in 65 and 43% of patients. In the course of etanercept + methotrexate therapy, infectious adverse events were more common. 12.7 and 7.3% of patients treated with etanercept and methotrexate discontinued their participation in the study during the first 6 months and 18 and 10% — during the first year. 8.4% of patients treated with the combination of etanercept and methotrexate discontinued their participation in the study during the second year.Conclusion: Etanercept monotherapy is effective on a par with the combination therapy, but it has a higher safety profile and a lower therapy «survival».